An overview on fundamentals of immediate release drug delivery system - Yogita Bundela; Dilip Agrawal; Gaurav Bhaduka (Creative Pharma Assent, 2022)
Tablet is most popular among all dosage forms today because of its convenience, ease of administration, greater flexibility in dosage form design, ease of production, and low cost and non-invasive therapy. Formulation of tablets requires API along with excipients. Excipients include lubricants, diluents, binders, glidants, disintegrants, sweetening agents, flavoring agents, etc. Recent trends indicate that multi-particulate drug delivery systems are suitable for achieving extended-release oral formulation with a low risk of dose dumping, mixing flexibility to attain difference release patterns, and reproducible and short gastric residence time. Modern technology in immediate-release tablets, such as novel granulation techniques and electrostatic dry powder coating techniques, are prevalent nowadays. Recently, the immediate-release formulation has been similar to various sustained-release formulations that are currently readily attainable.